Urban Statistics and Their Treatment and Use for Decision-Makers - Carr, Frank J. (Management Science, 1970)
While population growth and urbanization are the source of the problems of our cities, hoped for solutions lie in the management of our urban systems. Urban statistics are not only observations of the urban culture but the data used by decision-makers who cope with the individual problems of traffic, pollution, crime and education. The urban information system is characterized by many subsystems having functional and jurisdictional boundaries which defy integration in the commonly understood sense of the word as used in information systems parlance. However, integration of subsystems, in effect, if not in form, can be achieved through the appropriate design of interfaces among the subsystems and with the user. This paper describes such a network design for a national system. The approach outlined and the techniques described would in principle be equally applicable to systems at the state or local level.